Sustainable Energy Service Model and Solar Technology Intervention for Drying Fish: A Case Study from SELCO and VIEWS from South Odisha - Shiv Sankar Das, Debashree Debadatta Behera (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Energy is the solution to all problems in the world. It helps in human development to economic development of any region, state or country. Access to energy is a common problem in today’s era. Access to energy can help in brining prosperity to earning livelihood. This paper consists of two sections. The first section focuses on a sustainable energy service model where a Digital Service Centre (DSC) was set up in rural areas of South Odisha. It helped in changing the life of a rural youth. Similarly, the second section focuses on designing and developing a solar dryer which was used by fisherwomen for earning their livelihood in the rural areas of South Odisha. In the current research, a descriptive case method was used and cases were selected in a purposive manner. Data was collected for understanding the theoretical concepts of actors, factors and linkages among them and developing the conceptual framework. An action research method (of partial intervention in the ecosystem for applicability of the framework) has been undertaken. Various actors and factors were found out and their linkages were established among them. A novel approach of clean energy intervention for income generation, a sense of entrepreneurial mindset was developed and an enabling environment for intervention of clean energy products and services in rural areas was created.